Gene expression in a rarely studied intraabdominal adipose depot, the round ligament, in severely obese women: A pilot study. (3rd February 2016) - Mauriège, P.; Joanisse, D.R.; Cartier, A.; Lemieux, I.; Bergeron, J.; Biron, S.; Marceau, P.; Richard, D.
ABSTRACT: Gene expression (qPCR) was compared in round ligament (RL), omental (OME) and mesenteric (MES) ATs from 48 severely obese women (BMI, 54±11 kg/m 2 ; 38±9 yrs). The mRNA levels of enzymes of lipid metabolism (LPL, HSL, and PDE-3B), cortisol production (11βHSD-1), adipogenesis (PPAR-γ1/2), thrombosis and inflammation (PAI-1, IL-6, TNF-α and adiponectin) were determined. AT-LPL mRNA was highest in RL. The highest PDE-3B and lowest PAI-1 mRNA levels were observed in RL and MES. The lowest IL-6 and TNF-α and the highest adiponectin and PPAR-g1/2 mRNA levels were found in RL AT. 11βHSD-1 was highest in RL and OME. A higher lipogenic and adipogenic, and lower pro-inflammatory and pro-thrombotic profiles of the RL suggest a lesser deleterious impact on obesity-related complications.